DOI: 10.47749/t/unicamp.2018.1082269
|View full text |Cite
|
Sign up to set email alerts
|

Geocronologia U-Pb em zircão de ortognaisses e granitoides

Abstract: nasceu e foi criado em Sumaré, interior de São Paulo. Filho de migrantes rurais sem terras do sul de Minas Gerais, concluiu formação básica em colégio público, cursou aprendizagem industrial e curso técnico em eletroeletrônica na escola Senai Roberto Mange em Campinas (2002). Cursou bacharelado em geologia (2015) pela Universidade Estadual de Campinas (Unicamp). Desenvolveu seu Trabalho de Conclusão de Curso em Betânia do Piauí (PI), estudando sequências metassedimentares do Complexo Santa Filomena, na faixa m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…K-feldspar halo and quartz+calcite+chlorite veins with sericitic halo;(3) carbonatization with calcite+fluorite+sulfides veins; (4) silicification, pervasive and in veins; and(5) propylitic alteration with epidote and calcite veins. The mineralization is hosted in stages 1 and 3, where it occurs mostly as particles or filling fractures in the pyrite crystals and related with Te-Bi-Ag phases.Paragenetic studies of the mineralization combined with microprobe analysis indicated successive stages of pyrite formation defined in four generations: euhedral porous form the earliest generation, developed in the earliest veins from potassic alteration (py1).…”
mentioning
confidence: 99%
“…K-feldspar halo and quartz+calcite+chlorite veins with sericitic halo;(3) carbonatization with calcite+fluorite+sulfides veins; (4) silicification, pervasive and in veins; and(5) propylitic alteration with epidote and calcite veins. The mineralization is hosted in stages 1 and 3, where it occurs mostly as particles or filling fractures in the pyrite crystals and related with Te-Bi-Ag phases.Paragenetic studies of the mineralization combined with microprobe analysis indicated successive stages of pyrite formation defined in four generations: euhedral porous form the earliest generation, developed in the earliest veins from potassic alteration (py1).…”
mentioning
confidence: 99%